(3GdbGgQI GdSjfeGFjI(B: (3Yf GdeOjfI hGdMOGKI eG Hjf GdUhQI h hGdhGbY(B/ s - AlSayyad, Nizar (3GdUjGO, O(B. (3fRGQs ((3GdbGgQI; s (3GdeQGjG ddKbGaI hGdafhf; s, 2023)
Title translation: Cinematic Cairo: About the city and modernity between image and reality. (3cJGH (B"(3GdbGgQI GdSjfeGFjI(B: (3Yf GdeOjfI hGdMOGKI Hjf GdUhQI hGdhGbY(B" (3jbOe JGQjkNG dMOGKI eOjfI GdbGgQI HGSJNOGe GdCadGe cCOGI JMdjdjI hehVhY ddfbO, ehVkMG GdYdGbI Hjf GdeOjfI GdeGOjI hJUhQgG aj GdSjfeG(B. (3jQcR GdcJGH Ydi cjajI JUhjQ GdMjGI GdMVQjI hJMhdGJgG aj GdbGgQI efP HOGjGJ GdSjfeG GdeUQjI(B. (3jJfGhd GdbSe GdChd JWhQ GdYeQGf aj GdbGgQI ef NdGd CadGe ef GdKdGKjfjGJ MJi fgGjI GdbQf GdYTQjf, HjfeG jSJYQV GdbSe GdKGfj JCKjQ GdGbJUGO GdMQ hGddjHQGdj GdLOjO hGdCUhdjI GdOjfjI hGdJhJQGJ GdGLJeGYjI Ydi JUhjQ GdeOjfI(B. (3jhaQ GdcJGH JMdjdkG TGedkG dJWhQ GdMOGKI aj GdbGgQI, HGYJHGQgG EMOi Cge eOf GdYGde GdYQHj(B. The book Cinematic Cairo: On the City and Modernity Between Image and Reality presents a history of Cairo's modernity, using films as an analytical tool and a subject of critique. It explores the relationship between the physical city and its cinematic portrayal. The book examines how urban life and its transformations in Cairo have been depicted in Egyptian cinema since its early days. The first section focuses on the development of Cairo$1 (Bs urban landscape through films from the 1930s to the end of the 20th century, while the second section addresses the impact of free-market economics, neoliberalism, religious fundamentalism, and social tensions on the city's cinematic representation. The book offers a comprehensive analysis of Cairo$1 (Bs modernity as one of the most significant cities in the Arab world.s
Arabic
Keywords: NA9000-9428 Aesthetics of Cities. Urban planning and Beautifying; Cinematic representation (3GdJeKjd GdSjfeGFjs; Egypt- Cairo (3eUQ(B- (3GdbGgQIs